Zinc Oxide Nanoparticles Enhance the Tolerance and Remediation Potential of Bacillus spp. against Heavy Metal Stress. (14th September 2021) - Akhtar, Nazneen; Khan, Sehresh; Rehman, Shafiq Ur; Rehman, Zia Ur; Mashwani, Zia Ur Rehman; Rha, Eui Shik; Jamil, Muhammad
Abstract : Nanoparticles and bacteria have received a great attention worldwide due to their ability to remove heavy metals (HMs) from wastewater. The current study is aimed at finding the interaction of HMs-resistance strains ( Bacillus cereus and Lysinibacillus macroides ) with different concentrations (5, 10, 15, 20, and 25 mg/L) of zinc oxide nanoparticles (ZnO NPs) and how they would cope with HM stress (Pb, Cd, Cr, and Cu). The growth rate and tolerance potential of bacteria were increased at lowered concentrations (5 and 10 mg/L) of ZnO NPs against HMs while it was unaffected at higher concentrations of ZnO NPs. These findings were confirmed by minimum inhibition zone and higher zinc solubilization at lower concentrations of ZnO NPs. Scanning electron microscopy (SEM) revealed that higher concentrations of ZnO NP increased HM accumulation in bacteria cells which had a significant impact on bacterial morphology and caused pores in bacterial membrane while in the case of lower concentrations, the cell remained unaffected. These results were further supported by the less production of antioxidant enzymes (SOD, POD, and CAT), thiobarbituric acid reactive substances (TBARS), and hydrogen peroxide (H2 O2 ) contents at lower concentrations of ZnO NPs against heavy metal stress. This study suggested that synergistic treatment of Bacillus spp. with lower concentrations of ZnO NPs enhances the tolerance potential and significantly reduces the HM toxicity.